Identifikasi Kesalahan dan Miskonsepsi Mahasiswa Calon Guru Matematika Pada Topik SPLDV - Afriadi, Juli (Universitas Islam Negeri Imam Bonjol Padang, 2018)
This research aims to identify errors and misconceptions of prospective mathematics teacher students in the SPLDV material. This study uses a qualitative research design. Research data was collected from 15 micro teaching students in the sixth semester of UNP Padang, using test questions and interview guidelines The SPLDV test questions prepared include the concept of SPLDV with infinite solutions and SPLDV with exactly one solution. The results of the study indicate that there are a number of errors and misconceptions of the material. Identified student errors are conceptual errors, namely mistakes made by students because they do not understand the SPLDV concept properly. Strategic error, which is an error that occurs because students choose the wrong way to do it. Calculate errors, namely errors in performing mathematical operations. Systematic error, which is an error regarding the wrong selection of extrapolation techniques. The interview results show the causes of misconceptions experienced by students, namely ignorance, language errors, film shows, thinking skills, family background, parallel conceptions, and initial student misconceptions.Keywords: Misconception, SPLDV, Mathematics